Formation of sol–gel derived (Cu, Mn, Co)3O4 spinel and its electrical properties. Issue 10 (July 2017) - Mah, Joelle C.W.; Muchtar, Andanastuti; Somalu, Mahendra R.; Ghazali, Mariyam J.; Raharjo, Jarot
Abstract: An (Mn, Co)3 O4 spinel layer effectively suppresses Cr outward diffusion, but the occurrence of spallation between coating and metal interfaces and the increasing oxidation rate over time significantly deteriorate cell performance. A transition metal cation, particularly Cu, is added into the (Mn, Co)3 O4 to improve the long-term stability of the interconnect materials for low-to-intermediate-temperature solid oxide fuel cells (SOFCs). In this work, fine-crystalline (Cu, Mn, Co)3 O4 spinel powders with an average crystallite size of 21 nm were successfully synthesized via the citric acid–nitrate method. The potential for use as a coating material for low-to-intermediate-temperature SOFC interconnects was explored. According to the TG curves, IR spectra, and XRD patterns, 800 °C is recommended as the minimum calcination temperature for (Cu, Mn, Co)3 O4 spinel materials. Compared with (Mn, Co)3 O4 spinel materials, the addition of Cu does not induce significant changes in the crystal structure but markedly improves the electrical conductivity (116 Scm −1 ) and the activation energy (0.394 eV) of the (Cu, Mn, Co)3 O4 spinel. Overall, the sol–gel derived (Cu, Mn, Co)3 O4 spinel can be used as a coating material for low-to-intermediate-temperature SOFC interconnects and is superior to (Mn, Co)3 O4 spinel because high electrical conductivity is preferred to minimize ohmic losses between the electrodes of adjacent cells.